2022
DOI: 10.3390/ijms23020735
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Neuronal Necroptosis Mediated by RIPK1 Provides Neuroprotective Effects on Hypoxia and Ischemia In Vitro and In Vivo

Abstract: Ischemic brain injury is a widespread pathological condition, the main components of which are a deficiency of oxygen and energy substrates. In recent years, a number of new forms of cell death, including necroptosis, have been described. In necroptosis, a cascade of interactions between the kinases RIPK1 and RIPK3 and the MLKL protein leads to the formation of a specialized death complex called the necrosome, which triggers MLKL-mediated destruction of the cell membrane and necroptotic cell death. Necroptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…23 Subsequently, the MLKL binds to the cell membrane, causing a hole in the cell membrane, thereby triggering necroptosis. 24 Accumulating evidence suggests that cognitive impairments are associated with Alzheimer disease (AD), 21,25,26 specifically neuronal loss in the hippocampal CA1 regions. 27 In our study, protein expression levels of p-RIPK3/RIPK3 and p-MLKL/MLKL were meaningfully increased in hippocampal tissue of SAE mice.…”
Section: Discussionmentioning
confidence: 99%
“…23 Subsequently, the MLKL binds to the cell membrane, causing a hole in the cell membrane, thereby triggering necroptosis. 24 Accumulating evidence suggests that cognitive impairments are associated with Alzheimer disease (AD), 21,25,26 specifically neuronal loss in the hippocampal CA1 regions. 27 In our study, protein expression levels of p-RIPK3/RIPK3 and p-MLKL/MLKL were meaningfully increased in hippocampal tissue of SAE mice.…”
Section: Discussionmentioning
confidence: 99%
“…Only in the last decade, the attention of researchers was switched to the study of neural networks as the main functional units of the CNS responsible for the implementation of processing, storage and transmission of information, as well as for the implementation of higher cognitive functions, including memory, consciousness and emotional reactions [ 45 ]. This approach, using modern methods of neurobiology, makes it possible to analyze the tiny mechanisms of restructuring of the functional architectonics of neural networks under hypoxic damage, as well as the contribution of each element of the network to the development of the functional network response to the stress factor [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were studies conducted on the potential therapeutic effect of Nec-1 in many diseases affecting all organ systems. Briefly, the neuroprotective effect of necrostatin in ischemic injuries (Liu et al, 2019a;Mitroshina et al, 2022), hydrocephalus (Liu et al, 2021a), mitochondrial dysfunction (Apaijai et al, 2021), intracranial hypertension (Qian et al, 2022) was revealed. Necrostatin reduces postoperative cognitive dysfunction (Yin et al, 2022), neonatal neurotoxicity (Xu et al, 2021b), and cardiotoxicity (Erdogmus Ozgen et al, 2022).…”
Section: Ripk1 Inhibitorsmentioning
confidence: 99%